2004
DOI: 10.1269/jrr.45.447
|View full text |Cite
|
Sign up to set email alerts
|

Aloe Polysaccharides Mediated Radioprotective Effect through the Inhibition of Apoptosis

Abstract: Polysaccharides from aloe are always considered an effective radioprotector on irradiation-induced skin damage. The aim of this study was to determine if aloe polysaccharides (AP) have radioprotective effects on normal human cells in vitro and mouse survival in vivo and to explore the mechanism. Pretreatment with 50 microg/ml AP could improve the surviving fraction at 2 Gy (SF2) of three normal cell lines 293, ECV304, and C. liver from 41.5%, 46.5%, and 40.9% to 49.4%, 72.1%, and 89.1%, respectively. AP could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…Gpx, GR, GST and SOD activities were significantly increased in the X‐ray‐irradiated group when compared to the control group, which could be due to excessive generation of free radicals, and in an attempt to scavenge these, A. vera ‐pre‐treated X‐ray‐irradiated group exhibited significant decrease when compared to the X‐ray‐irradiated mice. It has been previously reported that A. vera conferred protection against X‐ray‐induced damage in animals (Rowe, ; Wang et al., ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Gpx, GR, GST and SOD activities were significantly increased in the X‐ray‐irradiated group when compared to the control group, which could be due to excessive generation of free radicals, and in an attempt to scavenge these, A. vera ‐pre‐treated X‐ray‐irradiated group exhibited significant decrease when compared to the X‐ray‐irradiated mice. It has been previously reported that A. vera conferred protection against X‐ray‐induced damage in animals (Rowe, ; Wang et al., ).…”
Section: Discussionmentioning
confidence: 95%
“…Aloe first gained popularity with report of its success in treating X‐ray burns in United States in 1930s (Rowe, ). Polysaccharides from Aloe conferred protection against X‐ray‐induced skin damage in mice (Wang et al., ). Aloe vera extract had exhibited radioprotective ability against gamma radiation‐induced testicular damage in experimental animals (Gehlot et al., ; Purohit et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It exerts its protective effect through suppression of oxidative stress and free radicals, acceleration of lipolysis and inhibition of inflammatory response Parmar et al 2010). A study conducted by Wang et al, (2004) demonstrated that Aloe vera polysaccharides exert its protective effect through the inhibition of apoptosis which is mediated by inhibition of pro-apoptotic protein expression and over expression of anti-apoptotic proteins with a subsequent inhibition of apoptosis and cell cycle disruption.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the Chinese herbal preparation, Yangyin Humo Decoction (YHD), was able to alleviate the oral mucomembranous reaction to radiation applied to patients with head-neck tumors (26). In addition, aloe polysaccharides (AP) have demonstrated radioprotective effects by blocking the upregulation of pro-apoptotic p53, Bax and Bad, and the downregulation of Bcl-2, in normal human cells in vitro and in mice in vivo (27). …”
Section: Tcm and Radiotherapymentioning
confidence: 99%